The Gap in Utilizing Zakat as Tax Deduction: A Socio-Legal Review of Religiosity, Knowledge, and Law Awareness - Prakoso, Dwi Hantoro; Widiastuti, Arum (SASI, 2025)
Introduction: Taxpayers in Indonesia, particularly in Malang Regency, are subject to various tax obligations. Among these, the integration of zakat—an Islamic form of almsgiving—as a deductible item in tax calculations presents both opportunities and challenges. Although formal regulations permit zakat to be deducted from taxable income, the extent to which this facility is understood and effectively utilized by taxpayers remains unclear. The interplay of religiosity, legal knowledge, and awareness significantly influences taxpayer behavior concerning zakat deductions.Purposes of the Research: This research aims to analyze the religiosity, knowledge and legal awareness of taxpayers in Malang Regency in utilizing zakat facilities as a tax deduction, as well as exploring taxpayers' perceptions of the zakat policy as a tax deduction.Methods of the Research: The research method used is a socio-legal approach with qualitative analysis. Qualitative analysis was carried out to understand religious values, social context, and taxpayer perspectives in utilizing zakat facilities as a tax deduction.Results of the Research: The research results show that while taxpayers in Malang Regency consistently fulfill their zakat and tax obligations, their understanding of zakat as a tax deduction is limited. Most respondents recognize the importance of knowing tax laws, but many lack full comprehension of how to calculate taxes when deducting zakat. The research highlights the need to strengthen legal knowledge and awareness through tax law literacy programs. It recommends collaboration between the government, the Directorate General of Taxes, and universities to improve taxpayer understanding and compliance.